Working Capital Management and Performance of Industrial and Consumer Goods Firms in Nigeria: A Comparative Analysis - Olaoye; Clement Olatunji; Adeboboye; Roseline (Information Management and Business Review, 2019)
This study conducted a comparative analysis on working capital management and performance of industrial and consumer goods firms in Nigeria. Precisely, the study compared effect of average collection period and average payment period on return on capital employed of selected industrial goods and consumer goods firms. 20 firms were randomly selected over a period of 10 years data were collected from annual report of the firms. This study used static data analyses to analyze data. Result showed average collection period and average payment period exert insignificant positive effect on return on capital employed of industrial goods firms, while both average collection period and average payment period exert insignificant negative effect on return on capital employed of consumer goods firms. Independent t-test result showed significant mean difference between coefficient estimate corresponding to industrial and consumer goods firms. This study concluded that there exists significant difference between the effect of working capital management on performance of industrial goods firms and consumer goods firms when performance is measured in terms of return on capital employed. Hence firms in both sub-sectors should be strategic when managing working capital, by setting higher average payment period in a manner that will not crowd-out their credit worthiness.